2020
DOI: 10.3390/d12080296
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Human Interference on Zooplankton and Fungal Diversity in Poyang Lake Watershed in China

Abstract: The Poyang water system in Jiangxi Province, China, is important for floodwater storage, diversity maintenance, and the economy of the Poyang Lake watershed. In recent years, pollution has destroyed the ecosystem and impacted human health and the related economy. The water quality of the Poyang Lake watershed and the impact of human interference must be assessed. Conventional analysis and high-throughput sequencing were used to evaluate the structure of both zooplankton and fungi in six sub-lakes of the Poyang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…The results showed that the combined OTU‐table of the same zooplankton species from the Poyang Lake Basin was categorized into 92 species, 45 genera, 26 families, eight orders, four classes, and two phyla using DNA metabarcoding, which was similar to a recent study using traditional biomonitoring methods (Chen et al, 2020 ; Lu et al, 2021 ; Lv, 2019 ). In addition, rotifers constitute the most diverse group within the zooplankton community using traditional biomonitoring methods (Chen et al, 2020 ; Hu et al, 2019 ; Lu et al, 2021 ; Lv, 2019 ; Qin et al, 2020 ), and DNA metabarcoding in this study also revealed rotifers as the most diverse group.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The results showed that the combined OTU‐table of the same zooplankton species from the Poyang Lake Basin was categorized into 92 species, 45 genera, 26 families, eight orders, four classes, and two phyla using DNA metabarcoding, which was similar to a recent study using traditional biomonitoring methods (Chen et al, 2020 ; Lu et al, 2021 ; Lv, 2019 ). In addition, rotifers constitute the most diverse group within the zooplankton community using traditional biomonitoring methods (Chen et al, 2020 ; Hu et al, 2019 ; Lu et al, 2021 ; Lv, 2019 ; Qin et al, 2020 ), and DNA metabarcoding in this study also revealed rotifers as the most diverse group.…”
Section: Discussionsupporting
confidence: 61%
“…Spatial changes in the zooplankton in our study were similar to those in studies based on traditional biomonitoring methods (Chen et al, 2020 ; Lu et al, 2021 ; Lv, 2019 ). Some studies have shown that habitat variability of the Poyang Lake Basin could affect the community structure of zooplankton based on traditional biomonitoring methods (Lu et al, 2021 ; Lv, 2019 ; Qin et al, 2020 ). Indeed, the habitat diversity of the lake area is higher than that of the other sampling areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species number, abundance, biomass, and α diversity of zooplankton were the highest in summer rather than during the other sampling periods. This may be attributed to the favorable summer temperatures, and phytoplankton was abundant in summer for increasing the number of zooplankton (Liu et al, 2020 ; Qin et al, 2020 ). In addition, the floodplain lake habitats became more complex in different seasons due to the presence of different morphological types of aquatic macrophytes (emergent, floating, rooted with floating leaves and submerged; Liu, 2016 ; Thomaz et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anthropogenic factors for changes in the water body area of Poyang Lake mainly include policy and economic factors [39]. The construction of Three Gorges Dam in 1994 had certain influence on the change of water body area in Poyang Lake.…”
Section: Links Between Driving Factors and Water Body Area Variationmentioning
confidence: 99%